Comparison of the Contamination Rate and Risk Factor Profile of Blood Culture Done in Emergency Department and MHDU/MICUs (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: blood culture; medical intensive care unit (MICU); medical high dependency unit (MHDU); emergency departments (EDs)